2016
DOI: 10.46538/hlj.13.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Heritage Speakers Follow All the Rules: Language Contact and Convergence in Polish Devoicing

Abstract: We use a comparative variationist framework to compare variable word-final obstruent devoicing patterns in heritage Polish, English and homeland Polish in conversational speech. Phonological and lexical factors are shown to condition this variation differently in the three varieties. We have a particular interest in one other factor relevant to heritage speakers: the amount of code-switching between Polish and English by each speaker. We show that, for second generation heritage speakers, individuals’ code-swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Relevant data is provided in the appendix. This echoes the lack of correlation of ethnic orientation to other variable linguistic patterns examined in the HLVC project (Lyskawa, 2015; Lyskawa, Maddeaux, & Melara, 2015; Nagy et al, 2014).…”
Section: Results: F0mentioning
confidence: 60%
“…Relevant data is provided in the appendix. This echoes the lack of correlation of ethnic orientation to other variable linguistic patterns examined in the HLVC project (Lyskawa, 2015; Lyskawa, Maddeaux, & Melara, 2015; Nagy et al, 2014).…”
Section: Results: F0mentioning
confidence: 60%
“…For Polish, voiced obstruents undergo a neutralization process and devoice word finally (Iverson and Salmons 2011;Łyskawa et al 2016). This operation does not occur before voiced obstruents, likely due to regressive spreading of GT from the onset of the following word.…”
Section: Ambiguous Surface Patterns: Wisconsin Frisianmentioning
confidence: 99%
“…However, in other areas they show variability that is different from monolingual norms (Alvord & Rogers, 2014; Amengual, 2016; Colantoni et al, 2016; Godson, 2004; Henriksen, 2015; Robles-Puente, 2014; Ronquest, 2012, 2013). Studies have found that heritage language vowel space either shows assimilation to or dissimilation from that of the majority language (Cummings Ruiz, 2019; Ronquest, 2012, 2013) and that heritage language stop productions are affected by factors such as cognate status (Amengual, 2012), code-switching (Łyskawa, Maddeaux, Melara & Nagy, 2016), and speaker generation (Mayr & Siddika, 2018; Nodari, Celata & Nagy, 2019). Some phonological properties may also show both variability and stability.…”
Section: Understanding Heritage Phonological Grammarsmentioning
confidence: 99%